SOCIAL SERVICES: ACHIEVEMENTS AND CHALLENGES IN THE ALBANIAN CONTEXT - Haxhiymeri, Edlira; Ndrio, Marina (Ревија за социјална политика/Journal of Social Policy, 2015)
The system of social services in Albania was totally transformedcompared to the system that functioned during the communist time.Besides State, various groups of civil society, strategic partners, donorsand international organizations played an important role in providingsocial services.The aim of this paper is a) to provide a general overview of therole of the actors that provide social services in Albania; b) to analyse theimpact of decentralization and privatization of social services; c) topresent evidence of achievements and challenges in the public and nonpublic services.The paper is not intended to be a comprehensive one on the overallsubject of the system of social services in Albania, but rather a review ofservices related to social protection of vulnerable groups, children andwomen support, services for the people with special needs.This paper is prepared based on documentation analysis (basicpolicy and strategic documents, legislation), interviewing and practicalexperience reflection. The documentation analysis has involved reviewing all readilyavailable materials, like domestic government policy documents, officialstatistics, national reports, publications of the NGO that offer socialservices and research publications on social services.The method for analyzing the information was content analysis.Ten key actors in Albania were interviewed for the purpose of thisresearch: five officials of the Ministry of Wellbeing and Youth and fiverepresentatives of NGO-s.The purpose of interviews was to gather information that is notpublicly available and to generate insights on the issue of social serviceprovision.It is a belief that the conclusions of this research will be acontribution to reshaping the role of all actors, increasing the role of thecivil society and private providers of social services and improving thequality of social services in Albania.
Keywords: social services; public and non public providers of social services